Gonadal hormones influence core body temperature during calorie restriction. Issue 2 (3rd April 2019) - Cintron-Colon, Rigo; Shankar, Kokila; Sanchez-Alavez, Manuel; Conti, Bruno
ABSTRACT: During calorie restriction (CR), endotherms adjust several physiological processes including the decrease of core body temperature (Tb ) and reduction of energy expenditure. We recently found that CR-induced hypothermia is regulated in a sex-dependent manner in mice with lowered central insulin-like growth factor receptor signaling. Here, we describe the contribution of sex hormones to CR-induced hypothermia in wild type C57BL6 mice by measuring Tb of female and male mice following bilateral gonadectomy and hormonal replacement. Specifically, we evaluated the effects of progesterone (P4), 17-ß estradiol (E2), a combination of both (P4 + E2) in females and of 5-α dihydrotestosterone (5-α DHT) in males. Gonadectomy resulted in an earlier and stronger CR-induced hypothermia in both sexes. These effects were fully antagonized in females by E2 replacement, but not by P4, which had only minor and partial effects when used alone and did not prevent the action of E2 during CR when both hormones were given in combination. 5-α-DHT had only minor and transient effects on preventing the reduction of Tb during CR on gonadectomized male mice. These findings indicate that gonadal hormones contribute to sex-specific regulation of Tb and energy expenditure when nutrient availability is scarce. Abbreviations : AL: ad libitum; ANOVA: analysis of variance; CR: calorie restriction; E2: 17-ß estradiol; GNX: gonadectomy or gonadectomized; IGF-1R: insulin-like growth factor 1 receptor; POA: preoptic area; P4: progesterone; RM: repeated measures; SD: standard deviation; SEM: standard error of mean; Tb : core body temperature; WT: wildtype; 5-α DHT: 5-α dihydrotestosterone.